Formulation and Evaluation of Vincristine Sulfate By Mucosal Drug Delivery for Advanced Chemotherapy - .Hariharan, M; Sangeetha, S.; Jaganathan, K. (Journal of Neonatal Surgery, 2025)
The present study focuses on the formulation and evaluation of a Vincristine sulfate delivery system intended for mucosal administration to enhance therapeutic efficacy and minimize systemic toxicity. The research aims to design, characterize, and assess the cytotoxic effects of the developed formulation on normal human cell lines using a series of in vitro assays. Cell viability, proliferation, and apoptosis were evaluated through MTT, Trypan Blue exclusion, and Propidium Iodide staining assays to determine dose-dependent cytotoxic responses. In addition, the antioxidant potential of the formulation was examined to explore its protective and therapeutic implications. Comparative analysis with conventional Vincristine sulfate delivery methods was performed to assess improvements in bioavailability and therapeutic index. The results are expected to provide insights into the formulation’s mechanism of action, safety profile, and overall efficacy. By addressing the limitations of traditional delivery routes, this mucosal Vincristine sulfate formulation represents a promising approach for enhancing cancer treatment outcomes. The findings of this research contribute to the broader understanding of Vincristine sulfate’s pharmacological potential and support the development of more effective and safer drug delivery strategies for oncology applications